45.5k views
3 votes
Show you work for full credit Use the SUBSITUTION method or ELIMINATION method to solve this system of equations:

Show you work for full credit Use the SUBSITUTION method or ELIMINATION method to-example-1
User Marchaos
by
5.7k points

2 Answers

4 votes
y=-2x+4
3x-2(-2x+4)=6
3x+4x-8=6
7x=14
x=2
y=-2x+4
y=-2(2)+4
y=0
User Quayshawn
by
6.2k points
5 votes
3x-2(-2x+4)=6
3x +4x-8=6

7x-8=6
Add 8 to both sides
7x=14
X=2. (2,
-3(2)+4=y
-6+4=y
-2=y

(2,-2)
User Hooray Im Helping
by
5.7k points